Pengaruh Motivasi dan Kompetensi Sdm Terhadap Kinerja Karyawan dengan Kepuasan Kerja Sebagai Variabel Intervening Pada Natus Eatery And Patisserie di Kota Payakumbuh - Rezki Valent; Vicky Brama Kumbara; Dimas Perdana Oskar (Jurnal Ekonomi dan Bisnis Digital, 2026)
This study aims to analyze the influence of leadership style and motivation on This study examines the effect of motivation and human resource competence on employee performance, with job satisfaction serving as an intervening variable at Natus Eatery and Patisserie in Payakumbuh City. A quantitative approach was employed using the Structural Equation Modeling (SEM) method based on SmartPLS to analyze the relationships among the research variables. The findings indicate that both motivation and human resource competence have a positive effect on employees' job satisfaction. Furthermore, motivation, human resource competence, and job satisfaction were found to have positive effects on employee performance. These results suggest that higher levels of work motivation and employee competence contribute to greater job satisfaction, which in turn enhances employee performance. Job satisfaction was also proven to act as an intervening variable, strengthening the relationship between motivation, human resource competence, and employee performance. The discussion reveals that strong work motivation encourages employees to demonstrate greater enthusiasm, responsibility, and productivity in completing their tasks. In addition, competent employees, supported by adequate knowledge, skills, and abilities, are more capable of performing their duties effectively and efficiently. Job satisfaction plays a significant role in fostering organizational commitment, loyalty, and a positive work environment, all of which contribute to improved employee performance. Therefore, employee performance is influenced not only by motivation and competence directly but also indirectly through job satisfaction. These findings imply that organizations should continuously invest in employee competency development, implement fair reward systems, and create a supportive work environment to enhance job satisfaction and achieve sustainable improvements in employee performance.